Genotype-integrated single-cell transcriptome analysis reveals the role of DDX41 pR525H in a patient with myelodysplastic neoplasms - Hirotaka Matsui; Akiko Nagamachi; Minori Koizumi; Rei Kudo; Masahiko Ajiro; Hironori Harada; Yuka Harada; Shigeyuki Shichino; Akihide Yoshimi (Scientific Reports)
Abstract DEAD-box helicase 41 (DDX41) is implicated in germline (GL)-predisposed myeloid neoplasms, where pathogenic GL variants often lead to disease following the acquisition of a somatic variant in trans, most commonly p.R525H. However, the precise molecular mechanisms by which DDX41 variants contribute to the pathogenesis of myeloid neoplasms remain poorly understood, partly due to challenges in establishing cellular and animal models that faithfully recapitulate the human disease phenotype. This limitation highlights the necessity of directly analyzing primary human disease cells. In this case report, conducted to pursue this objective, we implemented single-cell RNA sequencing integrated with genotyping at the p.R525 locus in a myelodysplastic neoplasm (MDS) harboring both germline and somatic DDX41 variants, leveraging highly efficient Terminator-Assisted Solid-phase cDNA amplification and sequencing. We found that acquiring p.R525H induced G2/M cell cycle arrest selectively in colony-forming unit-erythroid cells, accompanied by R-loop accumulation, which impaired erythropoiesis through DNA damage. In hematopoietic stem and myeloid progenitor populations, gene expression profiles were largely similar between p.R525H-positive and -negative cells. However, ligand-receptor interaction and transcriptional regulation analyses suggested a non-cell-autonomous influence from p.R525H-expressing cells on GL variant-only cells. This interaction drove convergence toward a shared expression profile, highlighting an intricate interplay shaping the patient’s MDS phenotype.